Comparison of the effects of gasoline burn and chromic acid burn on different internal organs and immune functions in rats: Effects of burn mechanism - Xu, Pei; Xu, Sida (Cellular and Molecular Biology, 2024)
Burn as physical injury ranks as the fourth most prevalent trauma across the world. In this study, we aimed to compare the impact of gasoline burn and chromic acid burn on the internal organs and immune functions in rats. The results showed that the levels of methemoglobin (MHb) to total hemoglobin (Hb) as well as the Cr6+ content showed significant elevation in the chromic acid burn group relative to the gasoline burn group. HE staining was used to evaluate the histological changes in the injured tissues as well as the tissues excised from internal organs. We found that chromic acid burn-induced more severe damage to rat tissues. Gasoline burn showed no significant impact on the intestinal tissues of rats, while the chromic acid burn-induced increased cell death in rat intestines. Moreover, the results of HE staining also revealed that gasoline burn and chromic acid burn showed no evident impact on rat hearts. Gasoline burn also showed no significant effects on the liver, lungs and kidneys of rats, while the chromic acid burn caused injuries to such internal organs in comparison with the control and gasoline burn groups. In addition, the MPO activity was higher in the liver, intestine, lungs and kidneys of rats with chromic acid burn. Furthermore, the expression of inflammation response cytokines was examined in the serum of rats. The results demonstrated that the levels of IL-6, IL-1β and TNF-α showed a significant increase in both the gasoline burn and chromic acid burn groups of rats relative to the control, and the levels were higher in the chromic acid burn group in comparison with the gasoline burn group. In conclusion, the chromic acid burn-induced more severe organ injury, inflammation and immune response compared with the gasoline burn, which may provide reference data for the clinical treatment of patients with different burn injuries.